Impact of a full-scale mass casualty exercise on hospital staff and implications for future preparedness: a pre-post study - Forst, Maik von der; Germann, Barbara J.; Schaefer, Hanne; Salg, Gabriel Alexander; Weigand, Markus A.; Schmitt, Felix; Dietrich, Maximilian; Mohr, Stefan; Küllenberg, Janna; Ries, Markus; Popp, Erik (Progress in disaster science, 2025)
Study hypothesis - Mass casualty incidents (MCI) can overwhelm hospital capacities. Effective management requires emergency plans and exercises to improve familiarity, confidence, and skills. Scientific evaluation of exercises is crucial to identify their impact, this study hypothesized indirect benefits for all staff from MCI exercises, even non-participants. - Methods - Two prospective, representative, anonymous surveys were conducted among all professional groups before and after a full-scale MCI exercise at Heidelberg University Hospital. Descriptive analyses were conducted for the total sample (N=669). Hierarchical linear regression analyses were performed for the dependent constructs Familiarity with MCI Plan, Familiarity with Alert Process, Knowledge of Tasks, and Knowledge about Roles and Cooperation. - Results - The exercise positively influenced knowledge of the MCI plan across all four constructs. Employees in management positions and physicians reported higher scores across all constructs. There appeared to be an overall improvement, suggesting that all employees have benefited. Greater significance was observed for theoretical than for practical knowledge. - Conclusions - There were significant improvements of theoretical and practical knowledge of the MCI plan after an exercise. All employees, including those without exercise participation, appeared to benefit, possibly due to increased awareness and enhanced preparation. However, these results cannot be conclusively attributed to the exercise itself.